2018
DOI: 10.1002/anie.201805543
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Light‐Triggered Soft Artificial Muscles via a Mixed‐Matrix Membrane Strategy

Abstract: Artificial muscles triggered by light are of great importance, especially for the development of non-contact and remotely controlled materials. Common materials for synthesis of photoinduced artificial muscles typically rely on polymer-based photomechanical materials. Herein, we are able to prepare artificial muscles using a mixed-matrix membrane strategy to incorporate photomechanical molecular crystals with connective polymers (e.g. PVDF). The formed hybrid materials inherit not only the advantages of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 38 publications
1
91
0
Order By: Relevance
“…[12] As ab ranch of stimuli-responsive actuation, photoactuators is particularly attractive for energy conversion, as they can be triggered externally in an on-invasive,n on-contact manner,a nd as such they are particularly attractive for practical applications. [10,14] Theactuation mechanism for photoinduced motion is well established for photoresponsive molecules,i ncluding diarylethene, [15] anthracene, [16] Schiff bases, [17] and azobenzene, [18] which undergo reversible shape deformations upon photoirradiation. [10,14] Theactuation mechanism for photoinduced motion is well established for photoresponsive molecules,i ncluding diarylethene, [15] anthracene, [16] Schiff bases, [17] and azobenzene, [18] which undergo reversible shape deformations upon photoirradiation.…”
mentioning
confidence: 99%
“…[12] As ab ranch of stimuli-responsive actuation, photoactuators is particularly attractive for energy conversion, as they can be triggered externally in an on-invasive,n on-contact manner,a nd as such they are particularly attractive for practical applications. [10,14] Theactuation mechanism for photoinduced motion is well established for photoresponsive molecules,i ncluding diarylethene, [15] anthracene, [16] Schiff bases, [17] and azobenzene, [18] which undergo reversible shape deformations upon photoirradiation. [10,14] Theactuation mechanism for photoinduced motion is well established for photoresponsive molecules,i ncluding diarylethene, [15] anthracene, [16] Schiff bases, [17] and azobenzene, [18] which undergo reversible shape deformations upon photoirradiation.…”
mentioning
confidence: 99%
“…Taking advantage of the reversibility of [4+4] cycloaddition reactions and the preferred π⋅⋅⋅π stacking manner, anthracene has emerged as one of the most attractive photoreactive groups for topochemical polymerization . In our previous report, we found that 1,2‐Bis[(anthracen‐9‐ylmethylene) amino] ethane (BA2DA) with two photoreactive anthracene blades linked by ethanediamine exhibited a head‐to‐head packing fashion with an anthracene‐anthracene distance of 3.981 Å (Figure ) which is suitable for [4+4] cycloadditions upon light irradiation. However, due to the inappropriate packing manner, they produced dimer or oligomers instead of ordered linear polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore,t he photoresponsive behavior of photoactuators fabricated via hybridization of molecular crystals with PVDF showed adaptable photoresponsive behavior (changing from "bending away from light" for BA2DA-PVDF to "bending toward light" for Pt-BA2DA-PVDF). [9] Finally,wedemonstrated the interesting photoactuator performance of Pt-BA2DA-PVDF, such as bending and crawling on the ground. Thes ynthesis strategy reported in this study to prepare large Pt-based polymer crystals is of broad scope,and is likely to be applied to other polymers.M oreover,t his study offers new approaches to utilize linear polymers for advanced applications such as the controlled release of drugs,a ctuators,a nd smart robots.…”
Section: Angewandte Chemiementioning
confidence: 92%